An exploration to agricultural diversification in India: A study of Bundelkhand region - Shekhar,; Gupta, Rashi; Verma, Parul (Asian Development Policy Review, 2024)
The study examines an exploration of agricultural diversification in India. Economic Survey 2022 calls for agriculture diversification in view of acute water stress in cultivated areas where wheat, paddy, and sugarcane are grown in India. Agriculture diversification has a direct association with farm income. Thus, it can substantially contribute to the income creation capacity of marginal and small farmers and stabilize their livelihoods. Thus, approaching this notion, a study aimed at an empirical analysis of agricultural diversification in the Bundelkhand region with the help of a primary survey. For this, a logit regression model has been used. With the implication of the logit model, it has been found that agriculture diversification is potentially and significantly more likely to be affected by the farm size, literacy, and agricultural training on technology demonstration. The study suggests restructuring education in rural areas and incorporating the aspect of regional agriculture literacy into the school curriculum. Special training or literacy programmes must be conducted specifically by targeting the small and marginal farmers, as the study found them more enthusiastic to adopt diversified agricultural practices. Further, there is an acute need to prevent ongoing land diminution, as excessively marginal land holdings are not effective and productive for diversified agricultural practices.